Taurodontism in association with the cusp of carabelli: a report of 2 cases - E. O. Sote; A. O. Ogunkola (Nigerian Dental Association, 2009)
Taurodontism is a malformation of multirooted teeth characterized by abnormally large pulp chamber and abnormally short roots. It is diagnosed by the use of radiographs. The cusp of Carabelli is a morphological anomaly of the crown usually seen clinically on the mesiopalatal surface of the maxillary first permanent molars. The aetiology of both anomalies is not entirely clear, however, both genetic and exogenous factors have been proposed. There are recent reports that mutation of some chromosomes could be a cause of taurodontism. Taurodontism has been reported along with talon cusp, dens evaginatus and some Syndromes. This paper presents an unusual occurrence of taurodontism in association with the cusp of Carabelli in a 15 year-old girl presenting with a toothache of 4 months duration and her 46 year-old mother. All the second permanent molars were taurodont. Other siblings investigated had cusps of Carabelli but no taurodont tooth. There was no associated syndrome in both mother and child. Root canal treatment of the pulpally involved taurodont mandibular left permanent second molar of the 15 year-old was carried out. Appropriate restorations were placed on all other carious molars. Her mother had no carious tooth. Taurodontism may present as pain when the affected tooth is carious or as a chance radiographic finding as it is the case in the mother. Preventive restorations of taurodont teeth is ideal treatment when detected early. The anthropological and clinical significance of the cusp of Carabelli is highlighted. The association of these two dental anomalies needs further investigation.